Temporal decline in the prognostic impact of a recurrent acute myocardial infarction 1985 to 2002. Issue 2 (29th August 2006) - Buch, P; Rasmussen, S; Gislason, G H; Rasmussen, J N; Køber, L; Gadsbøll, N; Stender, S; Madsen, M; Torp-Pedersen, C; Abildstrom, S Z
Abstract : Objective: To investigate trends in case-fatality and prognostic impact from recurrent acute myocardial infarction (re-AMI) during 1985–2002. Design: Retrospective cohort study using nationwide administrative data from Denmark. Settings: National registries on hospital admissions and causes of death were linked to identify patients with first AMI, re-AMI and subsequent prognosis. Patients: Patients ⩾30 years old with a discharge diagnosis of AMI during 1985–2002 were tracked for first hospital admission for re-AMI 1 year after discharge. Main outcome measures: One-year case-fatality. Results: 166 472 patients were identified with a first AMI; 14 123 developed re-AMI. One-year crude case-fatality from first AMI/re-AMI was 39% versus 43% in 1985–1989 and 25% versus 29% in 2000–2002, respectively. In 1985–89, 35 795 patients survived to discharge (71%); of these 2.5% experienced reinfarction within 30 days (early reinfarction) and an additional 9.0% reinfarction within days 31–365 (late re-AMI). Re-AMI carried a poor prognosis in 1985–1989 compared to no re-AMI with age- and sex-adjusted relative risk of 1-year case-fatality of 7.5 (95% CI: 6.9 to 8.5) from early re-AMI and 11.7 (95% CI: 11.0 to 12.4) from late re-AMI. In 2000–2002, 23 552 patients (86%) survived to discharge; 4.4% had early re-AMI and 6.6% late re-AMI. Adjusted relative risk of 1-year case-fatality had declined to 2.1 (95% CI: 1.9 to 2.5) from early re-AMI and 5.6 (95% CI: 5.1 to 6.2) from late re-AMI compared to patients without reinfarction. Conclusion: Prognosis after AMI has improved substantially during the latest two decades and extends to patients with re-AMI.